Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Usia Dewasa Dengan Intervensi Senam Kaki Diabetes Melitus Untuk Mencegah Komplikasi Neuropatik Diabetikum Pada Ibu R. - Nur Afifah; Rina Puspita Sari; Muhammad Hasan Basri; Alfika Safitri (Pusat Riset dan Inovasi Nasional, 2023)
Background Diabetes mellitus is a chronic disease that has a systemic impact on other organs due to peripheral vascularization disorders. The complication that is often experienced by people with diabetes mellitus is the occurrence of diabetic neuropathy, especially in the legs which is a burden on the family. Prevention of diabetic neuropathic complications is a simple action, one of which is diabetic foot exercise. Purpose of writing is to provide an overview of providing family nursing care with diabetes mellitus foot exercise interventions to prevent diabetic neuropathic complications The method used with the family nursing care process which consists of assessment, nursing diagnosis, intervention, implementation, and evaluation. The results show that family nursing problems arise, namely the risk of ineffective peripheral perfusion, ineffective family health maintenance and the risk of unstable blood glucose levels. The implementation results show that diabetes mellitus leg exercise can reduce the risk of diabetic neuropathy. Nurses can provide diabetic foot exercise to prevent the risk of diabetic neuropathic complications in providing family nursing care..